WOMEN IN MILITARY STRATEGY: A REVIEW OF WOMEN EMANCIPATION AND PROTECTION - Erlinda Matondang (Jurnal Pertahanan & Bela Negara, 2020)
Whether in conflict and war or peacebuilding, women are always considered victims of human rights violation and the vulnerable. In recent decades, there has been efforts to advocate for the protection of women's rights and women empowerment in the name of emancipation. This has allowed women's presence in several key sectors, including politics and military, resulting in a new role for women as resources in military strategy. This has put the policy to protect women during war into question, especially when women have now become a combatant. This paper analyzes this issue through two concepts (women protection and military strategy to understand the military's perception toward women's position and one theory (feminism) to understand women's perception toward their roles in the military during war. Therefore, the object of this observation is the role of women in military strategy with regard to the implementation of women' rights protection and military strategy. In this observation, this paper collects secondary data through literature review. Through this observation, we can have broader understanding of the role of women in military strategy because the primary purpose of this paper is to assess the possibility for changing women protection during war policy to reflect the current condition.Keywords: emancipation, human rights, military strategy, women protection